DIABETES MELLITUS IN PATIENTS FROM BURYAT POPULATION - T. P. Bardymova (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The paper considers specific features of type 1 Diabetes Mellitus in patients from Buryat populations. Characteristics of the incidence and prevalence of type 1 Diabetes Mellitus in patients of Buryat nationality are presented. Clinicalfeatures of type 1 Diabetes Mellitus in patients-buryats are highlighted. The aim of this study was to determine the ethnic characteristics of Diabetes Mellitus in patientsfrom Buryat population. It was found that the incidence and prevalence of type 1 Diabetes Mellitus in the Buryat population was below the relevant indicators of Russia and constituted 0.73 and 24.18 per 100 thousand population. Late vascular complications of the disease (diabetic nephropathy, diabetic retinopathy) occur in patients with type 1 Diabetes Mellitus of Buryat nationality less frequently than in the general population of patients with type 1 Diabetes Mellitus. Found that diabetic polyneuropathy (DP) was diagnosed in 25.8 % of patients.